Alzheimer's disease‐like neuropathology in three species of oceanic dolphin. (27th December 2022) - Vacher, Marissa C.; Durrant, Claire S.; Rose, Jamie; Hall, Ailsa J.; Spires‐Jones, Tara L.; Gunn‐Moore, Frank; Dagleish, Mark P.
Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease and the primary cause of disability and dependency among elderly humans worldwide. AD is thought to be a disease unique to humans although several other animals develop some aspects of AD‐like pathology. Odontocetes (toothed whales) share traits with humans that suggest they may be susceptible to AD. The brains of 22 stranded odontocetes of five different species were examined using immunohistochemistry to investigate the presence or absence of neuropathological hallmarks of AD: amyloid‐beta plaques, phospho‐tau accumulation and gliosis. Immunohistochemistry revealed that all aged animals accumulated amyloid plaque pathology. In three animals of three different species of odontocete, there was co‐occurrence of amyloid‐beta plaques, intraneuronal accumulation of hyperphosphorylated tau, neuropil threads and neuritic plaques. One animal showed well‐developed neuropil threads, phospho‐tau accumulation and neuritic plaques, but no amyloid plaques. Microglia and astrocytes were present as expected in all brain samples examined, but we observed differences in cell morphology and numbers between individual animals. The simultaneous occurrence of amyloid‐beta plaques and hyperphosphorylated tau pathology in the brains of odontocetes shows that these three species develop AD‐like neuropathology spontaneously. The significance of this pathology with respect to the health and, ultimately, death of the animals remains to be determined. However, it may contribute to the cause(s) of unexplained live‐stranding in some odontocete species and supports the 'sick‐leader' theory whereby healthy conspecifics in a pod mass strand due to high social cohesion. Abstract : Vacher et al used immunohistochemistry to look for Alzheimer's‐like pathology in the brains of aged long‐finned pilot whales, white‐beaked dolphins, Risso's dolphins, harbour porpoises and a bottle‐nosed dolphin that were found beached on the shores of Scotland. All aged animals had amyloid plaque pathology, and three species exhibited both plaques and accumulation of phosphorylated tau in neurons. The simultaneous occurrence of amyloid‐beta plaques and hyperphosphorylated tau in the brains of odontocetes shows that these three species develop Alzheimer's‐like neuropathology spontaneously.